Kirenol: A Potential Natural Lead Molecule for a New Drug Design, Development, and Therapy for Inflammation - Naurah Nabihah Nasir; Mahendran Sekar; Shivkanya Fuloria; Siew Hua Gan; Nur Najihah Izzati Mat Rani; Subban Ravi; M. Yasmin Begum; Kumarappan Chidambaram; Kathiresan V. Sathasivam; Srikanth Jeyabalan; Arulmozhi Dhiravidamani; Lakshmi Thangavelu; et al. (Molecules, 2022)
Kirenol, a potential natural diterpenoid molecule, is mainly found in Sigesbeckia species. Kirenol has received a lot of interest in recent years due to its wide range of pharmacological actions. In particular, it has a significant ability to interact with a wide range of molecular targets associated with inflammation. In this review, we summarise the efficacy and safety of kirenol in reducing inflammation, as well as its potential mechanisms of action and opportunities in future drug development. Based on the preclinical studies reported earlier, kirenol has a good therapeutic potential against inflammation involved in multiple sclerosis, inflammatory bowel disorders, diabetic wounds, arthritis, cardiovascular disease, bone damage, and joint disorders. We also address the physicochemical and drug-like features of kirenol, as well as the structurally modified kirenol-derived molecules. The inhibition of pro-inflammatory cytokines, reduction in the nuclear factor kappa-B (NF-κB), attenuation of antioxidant enzymes, stimulation of heme-oxygenase-1 (HO-1) expression, and nuclear factor erythroid 2-related factor 2 (Nrf2) phosphorylation are among the molecular mechanisms contributing to kirenol’s anti-inflammatory actions. Furthermore, this review also highlights the challenges and opportunities to improve the drug delivery of kirenol for treating inflammation. According to the findings of this review, kirenol is an active molecule against inflammation in numerous preclinical models, indicating a path to using it for new drug discovery and development in the treatment of a wide range of inflammations.